Interference effects in photoelectron asymmetry parameter (β) trends of C 2s−1 states of ethyne, ethene and ethane. (18th November 2016) - Decleva, Piero; Toffoli, Daniele; Kushawaha, Rajesh Kumar; MacDonald, Michael; Piancastelli, Maria Novella; Simon, Marc; Zuin, Lucia
Abstract: Photoelectron asymmetry parameters ( β ) of the gerade and ungerade C 2s −1 derived states of ethyne, ethene and ethane as a function of photon energy have been calculated and experimentally measured, to extend the search of interference effects on angular distributions to polyatomic molecules. The calculations cover the electron energy range from 0 to 1100 eV while the experimental measurements cover the electron energy range from 30 to 220 eV. Clear oscillations are interpreted in terms of interference of the photoelectron wave emitted from the two possible C 2s centres, or equivalently from the gerade and ungerade states associated with them. This is a microscopic analog of Young's double-slit experiment. The effect is however quite small and requires very high experimental accuracy to be detected. It is best evidenced in the behaviour of β difference between the two channels. The connection between β trends and structural parameters shows the expected inverse correlation between oscillation period and distance between the carbon atoms, but do not simply parallel the analogous behaviour found in cross sections.